ALIENASI DAN PEMBAKUAN PERAN GENDER - M.Hum, Istiadah (EGALITA, 2006)
The formal gender role in Indonesia is legitimized by laws, culture and religion. In family context, women’s role is contructed as a secondary and a complementary role altough women, basically, play an important role for the family continuity. Furthermore, cultural legitimacy which is regulated in the marital laws puts the role of women as alienated role, from the equal position with men to inequal one, in daily practices. As a result, married women’s position may be alienated in the family. This phenomena needs attention and deep disscussion from social scientists particularly those who are concerned with women issues (and moslems women) for the sake of gender equity as well as gender equility realization in Indonesia.